Characteristics of intussusception among children in Hokkaido, Japan, during the pre‐ and post‐rotavirus vaccine eras (2007–2016). (12th January 2023) - Fukuda, Yuya; Akane, Yusuke; Honjo, Saho; Kawasaki, Yukihiko; Tsutsumi, Hiroyuki; Tsugawa, Takeshi
Abstract: Aim: To analyse the epidemiology of intussusception in Hokkaido Prefecture, Japan during a 10‐year period spanning the introduction of the rotavirus (RV) vaccine (2007–2016). Methods: Using a standard questionnaire, a retrospective surveillance was conducted across 17 hospitals with paediatric beds in Hokkaido Prefecture. We compared the data between the pre‐vaccine era (2007–2011) and post‐vaccine era (2012–2016). Results: In total, 208 and 110 intussusception cases were in the pre‐ and post‐vaccine eras, respectively. A significant reduction of the intussusception incidence in children aged <1 year was observed from the pre‐ to the post‐vaccine era (102.4–56.5 per 100 000 infants; incidence rate ratio, 0.55; p = 0.004). There was a relatively high‐positive RV antigen detection rate (29.4%, 5/17) during the RV epidemic period in Japan (March–May) in the pre‐vaccine era. None of the intussusception cases in the 31 patients with a history of RV vaccination occurred within 1 month after the administration of an RV vaccine dose. Conclusions: The incidence of intussusception in children aged <1 year decreased significantly after RV vaccine introduction in Japan. Another survey is needed to determine how the incidence of intussusception has changed further since the introduction of routine RV vaccination in 2020.